Exploring the Therapeutical Potential of Asparagopsis armata Biomass: A Novel Approach for Acne Vulgaris Treatment - Adriana P. Januário; Carina Félix; Rafael Félix; Katie Shiels; Patrick Murray; Patrícia Valentão; Marco F. L. Lemos (Marine Drugs)
Acne vulgaris, a high-prevalence skin condition afflicting people, persists as a significant challenge in the absence of effective treatments and emerging antibiotic resistance. To address this pressing concern, exploration of innovative approaches is of the utmost importance. Asparagopsis armata, an invasive red seaweed renowned for its diverse array of bioactive compounds, emerges as a promising candidate. This study seeks to elucidate the potential utility of A. armata biomass in the treatment of acne vulgaris. Crude extracts were obtained through solid–liquid extraction, and fractions were obtained using liquid–liquid extraction. The analyzed bioactivities included antioxidant, antimicrobial, and anti-inflammatory. Also, chemical characterization was performed to identify free fatty acids and compounds through LC-MS and elements. The present findings unveil compelling attributes, including anti-Cutibacterium acnes activity, cytotoxic and non-cytotoxic effects, antioxidant properties, and its ability to reduce nitric oxide production with consequent anti-inflammatory potential. Additionally, chemical characterization provides insights into its mineral elements, free fatty acids, and diverse compounds. The observed antimicrobial efficacy may be linked to halogenated compounds and fatty acids. Cytoprotection appears to be associated with the presence of glycerolipids and glycosylated metabolites. Furthermore, its antioxidant activity, coupled with anti-inflammatory properties, can be attributed to phenolic compounds, such as flavonoids. This study underscores the potential of A. armata as a natural ingredient in skincare formulations, offering an important contribution to the ongoing battle against acne vulgaris.